FORMATION OF EFFECTIVE SYSTEM OF MANAGEMENT OF CORPORATE RIGHTS OF THE STATE - Radionova, N. V. (Science and Transport Progress, 2004)
The article considers the issues and main directions of formation of an effective control system over the state corporate rights in present-day market economy conditions inUkraine.